Optimal Fiscal and Monetary Policy with Nominal and Indexed Debt - Cosimano, Thomas (IMF Working Papers; Working Paper ;, 2003)
This paper highlights the importance of debt composition in setting optimal fiscal and monetary policy over short-run business cycles and in the long run. Nominal debt as state-contingent debt can be a significant policy tool to reduce the volatility of distortionary government policy, thereby reducing macroeconomic volatility while increasing equilibrium output and consumption. The welfare gain from using nominal debt to hedge against shocks to the government budget is as large as the welfare gain from the ability to issue debt.